Penatalaksanaan Hyperemesis Gravidarum dan Efektivitas Non Farmakologis Akupunktur: Literatur Review - Lilis Mamuroh; Furkon Nurhakim (Malahayati Nursing Journal, 2026)
ABSTRACT Hyperemesis gravidarum is a condition characterized by excessive nausea and vomiting, weight loss and electrolyte balance disorders, the mother looks thinner, skin turgor decreases and the eyes look sunken. Pregnant women in Indonesia experience nausea and vomiting and hyperemesis gravidarum occurs in one until three percent of all pregnancies in Indonesia. One non-pharmacological intervention for hyperemesis gravidarum is acupuncture, which is considered to have the potential to reduce symptoms of nausea and vomiting. The aim of this research is to determine the effectiveness of acupuncture in pregnant women who experience Hyperemesis Gravidarum. This research uses a narrative review method with the PICO approach, analyzing seven journals published between 2019-2024, from databases such as ScienceDirect and EBSCOhost. Various non-pharmacological interventions have varying potential and benefits in their effectiveness in treating hyperemesis gravidarum. However, in general acupuncture has been proven to be effective in reducing the frequency of nausea and vomiting and reducing the need for hospitalization. The PC6 acupuncture point provides significant benefits in alleviating symptoms. The combination of acupuncture with conventional therapy shows better results than either approach alone. Acupuncture side effects are minimal, with low cost and easy application. Acupuncture is a safe and effective intervention for treating hyperemesis gravidarum, helping to improve the quality of life of pregnant women by minimizing symptoms and complications. Keywords: Acupuncture, Hyperemesis gravidarum, Nausea, Vomiting.  ABSTRAK Hyperemesis gravidarum merupakan suatu keadaan yang ditandai rasa mual dan muntah yang berlebihan, kehilangan berat badan dan gangguan keseimbangan elektrolit, ibu terlihat lebih kurus, turgor kulit berkurang dan mata terlihat cekung. Wanita hamil di Indonesia mengalami mual muntah dan hyperemesis gravidarum terjadi pada satu hingga tiga persen dari seluruh kehamilan di Indonesia. Salah satu intervensi non-farmakologis untuk menangani hyperemesis gravidarum ini adalah akupunktur, yang dinilai memiliki potensi dalam mengurangi gejala mual dan muntah. Tujuan penelitian ini adalah untuk mengetahui efektivitas akupunktur pada Ibu hamil yang mengalami hyperemesis gravidarum. Penelitian ini menggunakan metode narrative review dengan pendekatan PICO, menganalisis tujuh jurnal yang diterbitkan antara tahun 2019-2024, dari basis data seperti ScienceDirect dan EBSCOhost. Berbagai intervensi non farmakologis memiliki potensi dan manfaat yang bervariasi efektifitasnya dalam penanganan hyperemesis gravidarum. Namun, secara umum akupunktur terbukti efektif mengurangi frekuensi mual dan muntah serta menurunkan kebutuhan rawat inap. Titik akupunktur PC6 memberikan manfaat signifikan dalam meredakan gejala. Kombinasi akupunktur dengan terapi konvensional menunjukkan hasil yang lebih baik dibandingkan pendekatan tunggal. Efek samping akupuntur minimal, dengan biaya rendah dan penerapan mudah. Akupunktur merupakan intervensi yang aman dan cukup efektif untuk mengatasi hyperemesis gravidarum, membantu meningkatkan kualitas hidup ibu hamil dengan meminimalkan gejala dan komplikasi. Kata Kunci: Akupunktur, Hyperemesis Gravidarum, Mual, Muntah.